Pengembangan Ensiklopedia Materi Vertebrata Kelas X SMA/MA sebagai Media Pembelajaran - Prycila Anggi Prasetia Hutagalung; Rahmadina Rahmadina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to develop a valid encyclopedia of vertebrate biodiversity and to receive positive responses from students and teachers at SMA Swasta Gajah Mada Medan. The research method used is Research and Development (R&D) with the Borg & Gall development model, which consists of 10 stages. The results show that media experts rated this product at 90%, categorized as